P388 CORONARY PLAQUE CHARACTERISTICS ASSOCIATED WITH MAJOR ADVERSE CARDIOVASCULAR EVENTS AMONG ATHEROSCLEROTIC PATIENTS AND LESIONS: A SYSTEMATIC REVIEW AND META–ANALYSIS. (18th May 2022) - Gallone, G; Bellettini, M; Gatti, M; Bruno, F; Scudeler, L; Cusenza, V; Lanfranchi, A; Angelini, A; De Filippo, O; Iannaccone, M; Prati, F; Porto, I; et al.
Abstract: Background: The clinical value of coronary plaque characteristics (CPCs) to inform intensified medical therapy or revascularization of non–flow–limiting lesion remains uncertain. We performed a systematic review and meta–analysis to study the prognostic impact of CPCs comprehensively assessed with invasive and non–invasive imaging technologies on patient–level and lesion–level major cardiovascular adverse events (MACE). Methods: We systematically reviewed MEDLINE, EMBASE, and the Cochrane database for studies evaluating the association of CPC with patient–level and lesion–level (MACE). CPCs included high plaque burden, low minimal lumen area, thin cap fibroatheroma, high lipid core burden index, low attenuation plaque, spotty calcification, napkin ring sign or positive remodelling. Results: Thirty studies (21 retrospective, 9 prospective) with 30.369 patients were included. CPCs were evaluated by invasive intravascular techniques in 9 studies (optical coherence tomography=4, intravascular ultrasound imaging=3, near–infrared spectroscopy intravascular ultrasound imaging=2) and by coronary computed tomography angiography (CCTA) in 21 studies. CPCs were significantly predictive of patient–level and lesion–level MACE, also when only adjusted data where considered. For each CPC, the odds appeared higher for lesion–level (HR range 3.2–16.8) as compared to patient–level MACE (HR range 1.8–4.1). Accuracy was modest to moderate for most CPCs at the patient–level (AUC for MACE ranging between 0.53 and 0.84) and moderate to good for most CPCs at the lesion–level (AUC for MACE ranging between 0.71 and 0.83). Plaques with more than one CPC had the highest accuracy for lesion–level MACE (AUC 0.87, 95%CI 0.84–0.90). CPC pooled sensitivities for lesion–level MACE ranged between 40% and 63% and specificities between 73% and 98%. As the pooled prevalence of CPCs among plaques was low (3% to 28%), the estimated positive predictive values for lesion–level MACE were modest (range 33% to 45%). Conclusion: CCTA and intravascular imaging characterization of CPCs provides independent prognostic value among atherosclerotic patients and lesions. However, the modest sensitivity and positive predictive value observed across all CPCs seem to suggest modest clinical value, especially to predict lesion–level events (PROSPERO identifier: CRD42021251810).